Segmentation of Liver from CT Abdomen using K-Means and Morphological Operations - Kiruthika, S; Kaspar Raj, I (International Journal of Computer Sciences and Engineering, 2025)
Liver plays a vital role in human body. In the present scenario, Liver related diseases affect large number of peoples in India. Segmentation of liver image from computed tomography helps in disease diagnosis and making pre-planning decisions for hepatic surgery. This paper presents a segmentation method with the combination of K-means clustering, thresholding and morphological operations. The proposed segmentation scheme is applied on a 2-dimentional computed tomography abdominal image and the experimental result is evaluated using Dice similarity co-efficient and the measure is 94.46% against gold standard image.